The Influence of Mental Health Literacy, Migration, and Education on the Duration of Untreated Psychosis - Naomi Takizawa; Ingrid Melle; Elizabeth Ann Barrett; Elizabeth Ann Barrett; Mari Nerhus; Mari Nerhus; Akiah A. Ottesen (Frontiers Media S.A., 2021)
Background: Duration of untreated psychosis (DUP) is associated with outcome in psychotic disorders and influenced by contextual factors such as immigration. Here we aimed to investigate the effect of mental health literacy (MHL) on duration of untreated psychosis considering the influence of migration and education.Methods: A total of 269 participants who received their first adequate medical treatment for a psychotic disorder within the current or past year were included to the Thematically Organized Psychosis study in Oslo, Norway. Sociodemographic and clinical information was collected through systematic interviews. MHL was measured as "recognition of psychotic symptoms" and assessed by "The Attitudes and Beliefs about Mental Health Problems" schizophrenia version. Influence of education, migration and MHL on DUP was analyzed with hierarchical block-wise multiple regression analysis.Results: Recognition of psychotic symptoms explained a small but unique variance (2.3%) in DUP after the effects of other important predictors were controlled for. Longer DUP was also associated with less education, lower premorbid social, and academic functioning, a diagnosis within schizophrenia spectrum disorder, and earlier age of onset. The model explained 26% of variance in DUP. Migration after the age of six and length of education were associated with MHL but did not have a significant interaction with MHL in predicting DUP.Conclusions: MHL, measured as recognition of psychotic symptoms, has a small but significant independent effect on DUP. The effect of MHL was larger than years of education and migration history, and did not interact with either, in predicting DUP. This suggests that MHL is an independent factor in prevention strategies for early psychosis.